Air Quality Evaluation Based on PM10 and PM2.5 Concentrations at the Entrance Gate of Kota Baru Parahyangan, West Bandung Regency - Wellid, Ismail (Jurnal Internasional Penelitian Teknologi Terapan, 2024)
Initially, Kota Baru Parahyangan was expected to have healthy air quality, because it is located far from the center of Bandung and the surrounding environment is still in the form of rice fields and small forests. However, because the entrance to Kota Baru Parahyangan is a confluence of vehicles from the west, east and the Padalarang toll gate, it causes severe vehicle congestion. The consequence of this density is an increase in PM10 and PM2.5 concentrations in the area. Therefore, the purpose of this study is to determine the air quality in the entrance gate area of Kota Baru Parahyangan. Particulate matter measurements of PM10 and PM2.5 were conducted for one week (7 days), from Monday to Sunday. There were three testing points carried out at the entrance gate area, namely at two points at the density location and one point towards the residential and business center. When evaluated using PP No. 22 of 2021, the measurement results show that the PM10 concentration for 7 days of measurement is still below the quality standard, but for PM2.5 there are 3 days where the concentration is above the quality standard. Meanwhile, when evaluated based on Permen LHK No. 14 of 2020, the average air pollutant standard index (ISPU) status for PM10 is “Medium” for points 1 and 2, and “Good” for point 3, but for PM2.5 the average status is “Medium” for all points. These results prove that the density of vehicles will have an impact on reducing air quality at points 1 and 2, while point 3, where the density of vehicles is relatively small compared to points 1 and 2, still has “Good” air quality for PM10. The relatively high concentrations of PM10 and PM2.5 at points 1 and 2 need to be addressed by the developers of Kota Baru Parahyangan and the West Bandung Regency government.